Evaluation of aggregate stability methods for soil health - Rieke, Elizabeth L.; Bagnall, Dianna K.; Morgan, Cristine L.S.; Flynn, Kade D.; Howe, Julie A.; Mac Bean, G.; Cappellazzi, Shannon B.; Cope, Michael; Liptzin, Daniel; Norris, Charlotte E.; Tracy, Paul W.; Aberle, Ezra; et al. (Geoderma, 2022)
•Four common indicators of aggregate stability were assessed across North America.•Aggregate stability indicators were moderately correlated with each other.•All indicators were influenced by inherent soil properties and climate.•Indicators were sensitive to tillage, cover crops, organic amendments, and residue.•Indicator responses to tillage were correlated with other soil health indicators. Aggregate stability is a commonly used indicator of soil health because improvements in aggregate stability are related to reduced erodibility and improved soil–water dynamics. During the past 80 to 90 years, numerous methods have been developed to assess aggregate stability. Limited comparisons among the methods have resulted in varied magnitudes of response to soil health management practices and varied influences of inherent soil properties and climate. It is not clear whether selection of a specific method creates any advantage to the investigator. This study assessed four commonly used methods of measuring aggregate stability using data collected as part of the North American Project to Evaluate Soil Health Measurements. The methods included water stable aggregates using the Cornell Rainfall Simulator (WSACASH), wet sieved water stable aggregates (WSAARS), slaking captured and adapted from SLAKES smart-phone image recognition software (STAB10), andthemean weight diameter of water stable aggregates (MWD).Influence of climate and inherent soil properties at the continental scale were analyzed in addition to method responses to rotation diversity, cash crop count, residue management, organic nutrient amendments, cover crops, and tillage. The four methods were moderately correlated with each other. All methods were sensitive to differences in climate and inherent soil properties between sites, although to different degrees. None measured significant effects from rotation diversity or crop count, but all methods detected significant increases in aggregate stability resulting from reduced tillage. Significant increases or positive trends were observed for all methods in relation to cover cropping, increased residue retention, and organic amendments, except for STAB10, which expressed a slightly negative response to organic amendments. Considering these results, no single method was clearly superior and all four are viable options for measuring aggregate stability. Therefore, secondary considerations (e.g., cost, method availability, increased sensitivity to a specific management practice, or minimal within-treatment variability) driven by the needs of the investigator, should determine the most suitable method.